Implementation Of The Independent Curriculum In Akidah Akhlak Learning To Train Students Critical Thinking - Salsabila Destian Dini; Rahmad Salahuddin Tri Putra (Institut Agama Islam An-Nawawi Purworejo, 2023)
This study aims to describe the application of learning akidah akhlak based on the merdeka curriculum to train students critical thinking, and describe the teachers way to train students critical thinking. This research was conducted at Muhammadiyah 11 Randegan Elementary School, with the research subjects being class teacher, akidah akhlak teachers, and fifth grade students. Data collection techniques through observation, interviews, and documentation. The data analysis technique uses a triangulation technique, which has a flow, namely data reduction, data presentation, and conclusion drawing. The results showed that the application of the merdeka curriculum in learning akidah akhlak, the teacher must integrate students critical thinking skills. The implementation of akidah akhlak learning begins with preliminary activities. Then the core activities in the form of exploration phases for students, core activities as a process of akidah akhlak teachers to hone, train, and develop students critical thinking skills, through several sparking questions, and closing activities. The strategy of the akidah akhlak teacher in training students critical thinking through strategies with discussion methods, problem-based learning, and through the project of strengthening the profile of pancasila students.